Effects of Traffic Cameras on Incident Management: Validation of Statistically Significant Effects Using Field Data. Issue 1 (January 2015) - Sun, Zhentian; Yu, Mingyuan; Wang, Hao; Li, Xuhong
In recent years the effectiveness of video cameras and other technology on incident management has been widely discussed. However, the statistically significant effects of traffic cameras in regard to incident management are still unclear to policy makers. This paper used real field data to test whether traffic cameras as independent devices have significant effects on freeway traffic incident detection, verification, and response. The traffic camera as the impact factor and field data are classified into two groups. After the possibility of using the parametric analysis of variance was excluded because of the nonnormal distribution of the field data, a nonparametric method, the Mann–Whitney U test, was used to examine the effects of traffic cameras on incident management. Traffic cameras as the impact factor were found to have statistically significant effects on freeway traffic incident detection, verification, and response. The analysis results in this paper can help policy makers understand the effects of traffic cameras better and can also help to promote the effectiveness of decision making in investing in video surveillance systems. In addition, this study provides an international perspective for understanding the role of traffic cameras and is a useful reference for researchers and policy makers in other countries.